Anticoagulation Therapy for Atrial Fibrillation - Hylek, Elaine M. (Seminars in Thrombosis and Hemostasis, 2013)
Atrial fibrillation (AF) is the most common significant cardiac rhythm disorder, and its prevalence is increasing worldwide. Atrial fibrillation confers a fivefold increased risk of stroke, and these strokes are associated with significant mortality and disability. The vitamin K antagonist, warfarin, has been the mainstay of anticoagulant therapy for patients with AF, reducing the risk of stroke by 65%. Despite its efficacy, warfarin remains underused in clinical practice because of its variable dose response, diet and medication interactions, and need for frequent monitoring. Stroke prevention in AF has entered an exciting therapeutic era with new classes of targeted anticoagulants that avoid the many pitfalls of the vitamin K antagonists. Dabigatran, an oral thrombin inhibitor, and the factor Xa inhibitors, rivaroxaban and apixaban, have demonstrated efficacy for stroke prevention and a reduced risk of intracranial hemorrhage relative to warfarin. Translating the efficacy of clinical trials into effective use of these novel agents in clinical practice will require an understanding of their pharmacokinetic profiles, dose selection, and management in select clinical situations.
Keywords: atrial fibrillation; anticoagulation; stroke; hemorrhage